Piezoelectricity of Bi2Se3 Nanosheet - Tingting Jia; Liu Yang; Juncheng Zhang; Hideo Kimura; Hongyang Zhao; Quansheng Guo; Zhenxiang Cheng (Nanomaterials, 2023)
Bi2Se3, one of the most extensively studied topological insulators, has received significant attention, and abundant research has been dedicated to exploring its surface electronic properties. However, little attention has been given to its piezoelectric properties. Herein, we investigate the piezoelectric response in a five-layer Bi2Se3 nanosheet using scanning probe microscopy (SPM) techniques. The piezoelectricity of Bi2Se3 is characterized using both conventional piezoresponse force microscopy (PFM) and a sequential excitation scanning probe microscopy (SE-SPM) technique. To confirm the linear piezoelectricity of Bi2Se3 two-dimensional materials, measurements of point-wise linear and quadratic electromechanical responses are carried out. Furthermore, the presence of polarization and relaxation is confirmed through hysteresis loops. As expected, the Bi2Se3 nanosheet exhibits an electromechanical solid response. Due to the inevitable loss of translational symmetry at the crystal edge, the lattice of the odd-layer Bi2Se3 nanosheet is noncentrosymmetric, indicating its potential for linear piezoelectricity. This research holds promise for nanoelectromechanical systems (NEMS) applications and future nanogenerators.